Spatial evaluation of speed-flow-geometry relationship on two-lane rural highways - Ibrahim, Muttaka Na (Asian Research Publishing Network, 2016)
The mean travel speed of drivers on uninterrupted flow facilities such as two-lane rural highways is deemed as good performance indicator for the subject road class; as the variable relates well with user perception. However, the operating conditions on two-lane roads relating to travel speed is different from those on other types of facilities, as fast moving vehicles in either direction are usually impeded by slower moving ones in the same travel direction and also facing oncoming traffic in the opposing lane. Thus, impeded vehicles may be compelled to travel at lower speeds than desired; particularly, in the absence of sufficient sight distance and permissible gap in the opposing traffic stream, being the appropriate lane used for passing maneuvers. This implies that the operating speed on two-lane highways substantially depends on the level of traffic flow and perhaps, its composition as well as the roadway geometric features. This paper examines the effects of traffic level, composition and road geometric features on the operating speed on two-lane highways based on a spatial approach. An empirical model relating mean travel speed to traffic flow parameters and highway geometric features was derived for prediction of mean travel speed on two-lane rural highways based on easily observable variables.